Factors Affecting Employee Performance and Their Impact on Employee Satisfaction in Hospitals: A Scoping Review - Samboe, Betania; Darmawan, Ede Surya (Jurnal Riset Kesehatan, 2025)
Delivering high-quality healthcare services relies on the performance of hospital staff. Various determinants, both internal and external, significantly impact this performance. While optimal performance typically fosters employee satisfaction, suboptimal performance can result in dissatisfaction, subsequently diminishing the overall organizational effectiveness of the hospital. The objective of this scoping review is to identify the factors influencing hospital employee performance and their satisfaction. This study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. Literature searches was performed across three major databases: Scopus, PubMed, and ProQuest databases. 1,332 literature items identified from the selected databases. The quality of the literature was assessed using the Joanna Briggs Institute Critical Appraisal Tools. Fifteen literatures included in this review was of medium quality (score 7-8) and high quality (score 9-10) This review identified factors affecting hospital employee performance. Internal factors affecting employee performance include emotional intelligence, work stress, digital stress, work-family conflict, benefits, housing, rewards, satisfaction, and spirituality. External factors affecting employee performance include environment, hospital type, organization, performance management system, work conflict, flexi-time, open communication, toxic leaders, planning, and team focus. It was concluded that a holistic understanding of these variables is essential for hospital management to enhance service quality and organizational performance.